Resilient high-toughness heat-conducting silica gel gasket and preparation method thereof

By using modified nanofibers and platinum catalysts in thermally conductive silicone gaskets to form a three-dimensional structure, the existing thermally conductive silicone gaskets are insufficient support and prone to deformation when the hardness is low, and the effects of high thermal conductivity, resilience and toughness are achieved, which are suitable for the heat dissipation needs of modern electronic products.

CN119505545APending Publication Date: 2025-02-25KUSN ZHONGDI MATERIALS TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411677159.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing thermally conductive silicone gaskets are difficult to provide good support when their hardness is low, and are prone to permanent deformation under external pressure, which cannot meet the needs of modern electronic products for low volatility, high thermal conductivity, high rebound and low hardness.

Method used

Polyvinyl silicone, hydrogen-containing silicone oil, homemade modified nanofibers, thermal fillers and platinum catalysts are used to form a three-dimensional structure by secondary abrading of the modified fibers, which improves the rebound performance and toughness of the silicone gasket.

Benefits of technology

It realizes the high thermal conductivity, resilience and toughness of thermally conductive silicone gaskets, can effectively support electronic components and maintain good rebound performance when under pressure, and is suitable for the heat dissipation needs of modern electronic products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a rebound high-toughness heat-conducting silica gel gasket and a preparation method thereof, and relates to the field of heat-conducting silica gel gaskets. According to the preparation method, fibers are taken as raw materials and are subjected to secondary grinding modification, and nanocrystallization cutting of the fibers is completed under the assistance of tungsten diselenide for the first time, so that more hydroxyl groups are exposed out of the fibers; 2-octenoic acid is added for secondary grinding, friction heat generated in the grinding process provides energy for modification of fibers by the 2-octenoic acid, the grafting efficiency of the 2-octenoic acid on nanofibers is improved, double bonds are introduced into a fiber molecular structure, so that the fibers can be crosslinked with polyvinyl siloxane, and the mechanical property of the fibers is improved. Finally, the rebound high-toughness heat-conducting silica gel gasket with the interior of a three-dimensional structure is prepared. The rebound high-toughness heat-conducting silica gel gasket prepared by the invention has efficient heat-conducting rebound effect and relatively high toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermally conductive silicone gaskets, and in particular to a resilient high-toughness thermally conductive silicone gasket and a preparation method thereof. Background Art

[0002] With the rapid development of the electronics industry, high-tech technologies such as electronic components, integrated circuit boards, and LEDs are increasingly tending to be denser and miniaturized. This trend requires that heat dissipation materials must not only have good thermal conductivity, but also be soft enough to better fit the surface of the heating element. The increase in the power density of electronic devices makes heat dissipation a key factor affecting the performance and life of electronic products. At present, most common thermal conductive silicone gaskets use alumina as a thermal conductive material, which can effectively improve the heat dissipation efficiency and ensure the stable operation of electronic products in high temperature environments. In order to maintain a high thermal conductivity, a high amount of addition is often used. However, this will make it difficult for the gasket to have a good supporting force when the hardness is low, and it is easy to permanently deform when it encounters a little external pressure. In view of the requirements of electronic products for low volatility, high thermal conductivity, high rebound and low hardness, it is urgent to develop thermal conductive gaskets that can meet the needs of modern electronic products. Summary of the invention

[0003] The object of the present invention is to provide a resilient high-toughness thermally conductive silicone gasket and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a resilient high-toughness thermally conductive silicone gasket, which comprises polyvinyl siloxane, hydrogen-containing silicone oil, self-made modified nanofibers, thermally conductive fillers, and catalysts.

[0005] Furthermore, the self-made modified nanofiber is made of fiber as raw material, nano-cutting is performed with the assistance of tungsten diselenide to obtain nano-fiber, and then 2-octenic acid and a cobalt-based catalyst are added and secondary grinding is performed to obtain the nano-fiber.

[0006] Furthermore, the viscosity of the polyvinyl siloxane is 2000-8000 mPa·s, and the weight percentage of hydrogen in the hydrogen-containing silicone oil is 0.2-0.4%.

[0007] Furthermore, the thermally conductive filler is one or more of aluminum oxide, boron nitride, silicon nitride, and magnesium oxide.

[0008] Furthermore, the catalyst is a platinum catalyst.

[0009] Furthermore, a method for preparing a resilient high-toughness thermally conductive silicone gasket comprises the following preparation steps:

[0010] (1) 10 to 20 parts of cotton fiber and 5 to 10 parts of tungsten diselenide are added to a ball mill reactor, and dry-mixed and ball-milled at a speed of 100 to 200 r / min for 3 to 6 hours under a nitrogen atmosphere. After the dry-mixed and ball-milled, 1 to 5 parts of 2-octenoic acid, 0.1 to 2 parts of a cobalt-based catalyst, and 50 to 80 parts of anhydrous ethanol are added to the ball mill reactor, and wet-mixed and ball-milled at a speed of 200 to 300 r / min for 3 to 6 hours at room temperature under a nitrogen atmosphere. After the reaction is completed, the mixture is taken out and centrifuged at a speed of 10,000 to 15,000 r / min, filtered under reduced pressure, and the filtrate is washed with water, and the mixture is centrifuged at a speed of 10,000 to 15,000 r / min and filtered under reduced pressure. This process is repeated 3 to 6 times to obtain a self-made modified nanofiber modified by two ball millings;

[0011] (2) Polyvinyl siloxane, hydrogen-containing silicone oil, self-made modified nanofibers, thermal conductive fillers, and catalysts are mixed and heated and stirred for reaction. After the reaction is completed, a thermal conductive silicone rubber material is obtained, which is rolled into a sheet with a thickness of 0.5 to 1.5 mm in a tablet press and cured at 110 to 140° C. for 10 to 40 minutes.

[0012] Furthermore, in the step (3), the mass ratio of polyvinylsiloxane, hydrogen-containing silicone oil, self-made modified nanofiber, thermal conductive filler and catalyst is 50-100:1-10:1-10:20-30:0.5-3.

[0013] Furthermore, in step (3), the heating temperature is 40-60° C., the stirring speed is 300-600 r / min, and the stirring time is 2-4 h.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0015] The resilient high-toughness thermally conductive silicone gasket prepared by the present invention effectively increases the resilience and toughness of the gasket on the basis of achieving the high thermal conductivity effect of the organic silicone gasket.

[0016] The invention uses fiber as a raw material and performs secondary grinding and modification. For the first time, tungsten diselenide is used to assist in completing the nano-cutting of the fiber, and more hydroxyl groups are exposed in the fiber. As the grinding time is prolonged, the tungsten diselenide and the nano-fiber are chemically bonded to each other, and the physical intercalation structure is accompanied to improve the bonding degree between the two, thereby improving the strength of the nano-fiber and further improving the mechanical properties of the organic silicon gasket. Then, 2-octenoic acid is added and the second grinding is performed. The friction heat generated during the grinding process provides energy for the modification of the fiber by 2-octenoic acid, stimulates the activity of amino groups and hydroxyl groups on the surface of the fiber, and improves the grafting efficiency of 2-octenoic acid on the nano-fiber, thereby introducing double bonds into the fiber molecular structure, enabling the fiber to be cross-linked with polyvinyl siloxane, and further presenting a three-dimensional structure inside the silicone gasket. The fiber serves as a connecting bridge. Since there are more methylene groups in the three-dimensional structure, when the fiber is subjected to pressure, the three-dimensional overall structure can be effectively driven to expand and contract and rebound, thereby improving the resilience of the silicone gasket. Moreover, since tungsten diselenide has good lubricity, the movement and rebound of the internal structure are easier, thereby enhancing the toughness and resilience of the silicone gasket. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the rebound high-toughness thermal conductive silicone gasket prepared in the following examples are as follows:

[0019] Thermal conductivity: According to ASTM D5470 standard, the thermal conductivity of the resilient high-toughness thermally conductive silicone gaskets prepared in Examples 1-3 and Comparative Examples 1-6 was measured;

[0020] Tensile strength and elongation at break: According to GB / T 528-2009 standard, the tensile strength and elongation at break of the resilient high-toughness thermally conductive silicone gaskets prepared in Examples 1-3 and Comparative Examples 1-3 were measured.

[0021] Example 1

[0022] (1) 10 parts of cotton fiber and 5 parts of tungsten diselenide were added to a ball mill reactor, and dry-mixed and ball-milled at a speed of 200 r / min for 5 h under a nitrogen atmosphere. After the dry-mixed and ball-milled, 1 part of 2-octenoic acid, 0.1 part of a cobalt-based catalyst, and 50 parts of anhydrous ethanol were added to the ball mill reactor, and wet-mixed and ball-milled at a speed of 300 r / min for 5 h at room temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was taken out and centrifuged at a speed of 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The mixture was centrifuged at a speed of 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain the homemade modified nanofibers modified by two ball millings.

[0023] (2) 50 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 1 part of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 1 part of homemade modified nanofibers, 20 parts of aluminum oxide, and 0.5 parts of a platinum catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120°C for 30 minutes.

[0024] Example 2

[0025] (1) 15 parts of cotton fiber and 8 parts of tungsten diselenide were added to a ball mill reactor, and dry-mixed and ball-milled at a speed of 200 r / min for 5 h under a nitrogen atmosphere. After the dry-mixed and ball-milled reaction, 3 parts of 2-octenoic acid, 1 part of a cobalt-based catalyst, and 60 parts of anhydrous ethanol were added to the ball mill reactor, and wet-mixed and ball-milled at a speed of 300 r / min for 5 h at room temperature under a nitrogen atmosphere. After the reaction was completed, the mixture was taken out and centrifuged at a speed of 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The mixture was centrifuged at a speed of 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain the homemade modified nanofibers modified by two ball millings.

[0026] (2) 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 8 parts of homemade modified nanofibers, 25 parts of aluminum oxide, and 1.5 parts of a platinum catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120°C for 30 minutes.

[0027] Example 3

[0028] (1) 20 parts of cotton fiber and 10 parts of tungsten diselenide were added to a ball mill reactor, and dry-mixed and ball-milled at a speed of 200 r / min for 5 h under a nitrogen atmosphere. After the dry-mixed and ball-milled reaction, 5 parts of 2-octenoic acid, 2 parts of cobalt-based catalyst and 80 parts of anhydrous ethanol were added to the ball mill reactor, and wet-mixed and ball-milled at a speed of 300 r / min for 5 h at room temperature under a nitrogen atmosphere. After the reaction was completed, the fiber was taken out and centrifuged at a speed of 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The fiber was centrifuged at a speed of 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain the self-made modified nanofibers modified by two ball millings.

[0029] (2) 100 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 10 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 10 parts of homemade modified nanofibers, 30 parts of aluminum oxide, and 3 parts of platinum catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120°C for 30 minutes.

[0030] Comparative Example 1

[0031] 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 25 parts of aluminum oxide and 1.5 parts of a catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a tablet press and cured at 120°C for 30 minutes.

[0032] Comparative Example 2

[0033] (1) 15 parts of cotton fiber, 3 parts of 2-octenoic acid, 1 part of cobalt-based catalyst, and 60 parts of anhydrous ethanol were wet-mixed and ball-milled at 300 r / min for 5 h at room temperature under a nitrogen atmosphere. After the reaction was completed, the cotton fiber was taken out and centrifuged at 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The filtrate was centrifuged at 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain 2-octenoic acid-modified nanofibers.

[0034] (2) 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 8 parts of 2-octenic acid-modified nanofibers, 25 parts of aluminum oxide, and 1.5 parts of a platinum catalyst were mixed, heated at 50° C. and stirred at a speed of 500 r / min for 4 h. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120° C. for 30 min.

[0035] Comparative Example 3

[0036] (1) 15 parts of cotton fiber and 8 parts of tungsten diselenide were added into a ball mill reactor, and dry mixed and ball milled at a speed of 200 r / min for 5 h under a nitrogen atmosphere. After the dry mixing and ball milling, tungsten diselenide modified nanofibers were obtained;

[0037] (2) 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 8 parts of tungsten diselenide modified nanofibers, 25 parts of aluminum oxide, and 1.5 parts of a platinum catalyst were mixed, heated at 50° C. and stirred at a speed of 500 r / min for 4 h. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120° C. for 30 min.

[0038] Comparative Example 4

[0039] (1) 15 parts of cotton fiber and 8 parts of tungsten diselenide were added to a ball mill reactor, and dry-mixed and ball-milled at a speed of 200 r / min under a nitrogen atmosphere for 5 h. After the dry-mixing and ball-milling, 3 parts of 2-octenoic acid, 1 part of a cobalt-based catalyst, and 60 parts of anhydrous ethanol were mixed, and allowed to stand at room temperature for 5 h under a nitrogen atmosphere. After the reaction was completed, the cotton fiber was taken out and centrifuged at a speed of 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The filtrate was centrifuged at a speed of 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain the homemade modified nanofibers modified by two ball millings;

[0040] (2) 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 8 parts of homemade modified nanofibers, 25 parts of aluminum oxide, and 1.5 parts of a platinum catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120°C for 30 minutes.

[0041] Comparative Example 5

[0042] (1) 15 parts of cotton fiber and 8 parts of tungsten diselenide were added to a ball mill reactor, and dry-mixed and ball-milled at a speed of 200 r / min for 4 h under a nitrogen atmosphere. After the dry-mixed and ball-milled, 3 parts of 2-octenoic acid, 1 part of a cobalt-based catalyst, and 60 parts of anhydrous ethanol were added to the ball mill reactor, and wet-mixed and ball-milled at a speed of 300 r / min for 5 h at room temperature under a nitrogen atmosphere. After the reaction was completed, the fiber was taken out and centrifuged at a speed of 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The fiber was centrifuged at a speed of 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain the self-made modified nanofibers modified by two ball millings.

[0043] (2) 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 8 parts of homemade modified nanofibers, 25 parts of aluminum oxide, and 1.5 parts of a platinum catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120°C for 30 minutes.

[0044] Comparative Example 6

[0045] (1) 15 parts of cotton fiber and 8 parts of tungsten diselenide were added to a ball mill reactor, and dry-mixed and ball-milled for 3 hours at a speed of 200 r / min under a nitrogen atmosphere. After the dry-mixed and ball-milled, 3 parts of 2-octenoic acid, 1 part of a cobalt-based catalyst, and 60 parts of anhydrous ethanol were added to the ball mill reactor, and wet-mixed and ball-milled for 5 hours at a speed of 300 r / min at room temperature under a nitrogen atmosphere. After the reaction was completed, the fiber was taken out and centrifuged at a speed of 12000 r / min, filtered under reduced pressure, and the filtrate was washed with water. The fiber was centrifuged at a speed of 12000 r / min and filtered under reduced pressure. This process was repeated 5 times to obtain the homemade modified nanofibers modified by two ball millings.

[0046] (2) 80 parts of polyvinyl siloxane with a viscosity of 5000 mPa·s, 6 parts of hydrogen-containing silicone oil with a hydrogen content of 0.3% by weight, 8 parts of homemade modified nanofibers, 25 parts of aluminum oxide, and 1.5 parts of a platinum catalyst were mixed, heated at 50°C and stirred at a speed of 500 r / min for 4 hours. After the reaction, a thermally conductive silicone rubber material was obtained, which was rolled into a sheet with a thickness of 1.5 mm in a sheet press and cured at 120°C for 30 minutes.

[0047] Effect example

[0048] Table 1 below shows the mechanical property test results of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0049] Table 1 Mechanical properties test results of Examples 1 to 3 and Comparative Examples 1 to 6

[0050] Thermal conductivity / (W / m·K) Tensile strength / (MPa) Elongation at break / (%) Example 1 12.3 3.3 370 Example 2 13.5 3.6 382 Example 3 11.9 3.1 375 Comparative Example 1 10.5 1.5 290 Comparative Example 2 10.2 2.5 340 Comparative Example 3 11.3 2.0 317 Comparative Example 4 11.2 2.3 319 Comparative Example 5 11.5 2.9 352 Comparative Example 6 11.1 2.7 331

[0051] From the mechanical property test results of Examples 1 to 3 and Comparative Examples 1 to 6 in Table 1, we found that the resilient high-toughness thermally conductive silicone gasket prepared by the present application has excellent thermal conductivity. The results of Comparative Example 2, Comparative Example 1, and Comparative Example 2 show that the fiber modified by tungsten diselenide and 2-octenoic acid makes the performance improvement of the thermally conductive silicone gasket more obvious, and the fiber modified by octenoic acid is added to the gasket, which brings a three-dimensional network structure with a more rebound effect to the gasket, and effectively improves the resilience and toughness of the gasket. The results of Comparative Example 2 Comparative Examples 5-6 show that in the process of tungsten diselenide assisting ball milling of fibers to nano-nize the fibers, the longer the ball milling time, the higher the degree of nano-nization, so that the thermally conductive silicone gasket finally formed has higher resilience and toughness. The results of Comparative Example 2 and Comparative Example 4 show that ball milling improves the combination of 2-octenoic acid and fibers, and finally effectively improves the mechanical properties of the gasket.

[0052] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-toughness and resilient thermally conductive silicone gasket, characterized in that: The resilient high-toughness thermally conductive silicone gasket comprises polyvinyl siloxane, hydrogen-containing silicone oil, self-made modified nanofibers, thermally conductive fillers, and catalysts.

2. The resilient high-toughness thermally conductive silicone gasket according to claim 1, characterized in that: The self-made modified nanofiber is made of fiber as raw material, nano-cutting is performed with the assistance of tungsten diselenide to obtain nano-fiber, and then 2-octenic acid and a cobalt-based catalyst are added to obtain the nano-fiber through secondary grinding.

3. The resilient high-toughness thermally conductive silicone gasket according to claim 1, characterized in that: The viscosity of the polyvinyl siloxane is 2000-8000 mPa·s, and the weight percentage of hydrogen in the hydrogen-containing silicone oil is 0.2-0.4%.

4. The resilient high-toughness thermally conductive silicone gasket according to claim 1, characterized in that: The thermal conductive filler is one or more of aluminum oxide, boron nitride, silicon nitride and magnesium oxide.

5. The resilient high-toughness thermally conductive silicone gasket according to claim 1, characterized in that: The catalyst is a platinum catalyst.

6. A method for preparing a resilient high-toughness thermally conductive silicone gasket, characterized in that: The method comprises the following preparation steps: (1) Add 10-20 parts of cotton fiber and 5-10 parts of tungsten diselenide into a ball mill reactor, dry-mix and ball mill for 3-6 hours at a speed of 100-200 r / min under a nitrogen atmosphere, then add 1-5 parts of 2-octenoic acid, 0.1-2 parts of a cobalt-based catalyst, and 50-80 parts of anhydrous ethanol into the ball mill reactor, wet-mix and ball mill for 3-6 hours at a speed of 200-300 r / min under a nitrogen atmosphere at room temperature, after the reaction is completed, take out the fiber, centrifuge at a speed of 10000-15000 r / min, filter under reduced pressure, wash the filtrate with water, continue to centrifuge at a speed of 10000-15000 r / min, filter under reduced pressure, repeat this process 3-6 times, and obtain the homemade modified nanofiber modified by two ball millings; (2) Polyvinyl siloxane, hydrogenated silicone oil, homemade modified nanofibers, thermal conductive fillers, and catalysts are mixed and heated and stirred for reaction. After the reaction, a thermal conductive silicone rubber material is obtained, which is pressed into a sheet with a thickness of 0.5 to 1.5 mm in a tablet press and cured at 110 to 140 °C for 10 to 40 min.

7. The method for preparing a resilient high-toughness thermally conductive silicone gasket according to claim 6, characterized in that: In the step (3), the mass ratio of polyvinyl siloxane, hydrogen-containing silicone oil, homemade modified nanofiber, thermal conductive filler and catalyst is 50-100:1-10:1-10:20-30:0.5-3.

8. The method for preparing a resilient high-toughness thermally conductive silicone gasket according to claim 6, characterized in that: In the step (3), the heating temperature is 40-60° C., the stirring speed is 300-600 r / min, and the stirring time is 2-4 h.